Workshop Secara Daring Sustainable Lifestyle Skala Rumah Tangga di Masa Pandemi Covid-19 - Tahyatul Bariroh; Sofia Fatmawati; Rindita (Institut Pertanian Bogor, 2022)
The environmet's condition as a place for humans and other living things is decreasing due to human activities. To overcome or delay that phenomenon, an eco-friendly lifestyle needs to be applied by everyone. This lifestyle is known as the green lifestyle or sustainable lifestyle. This community service activity aimed to introduce that lifestyle to the women of Aisyiyah local administrations (PDA) of North Jakarta. In this workshop, the lecturers of the Faculty of Pharmacy, Universitas Muhammadiyah Prof. DR. HAMKA gave the lecture about how to utilize and minimalize waste from household activity which is very useful in the pandemic era, when most of the family spent their activities at home. The main theme of this workshop is less-waste lifestyle, vegetable regrow from cooking waste and also the utilization of used cooking oil for making eco-friendly soap. Because of the pandemic situation, this workshop was held on the 2nd of January 2021 with web seminar method using Zoom meeting and the coordination was performed by WhatsApp group. Aside from PowerPoint slides and videos of eco-friendly soap making, the participant was given a post-test and an evaluation form at the end of the webinar. The duration of this webinar was 2 hours and the follow-up were carried out in the WAG, which is monitoring the participant's regrow results. From this activity, the post-test result showed that participants obtained an upgraded knowledge about the lecture given.